2021
DOI: 10.1029/2020jc016619
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Surf Zone Eddy Field and Cross‐Shore Exchange on a Nonidealized Bathymetry

Abstract: The nearshore ocean spans the cross-shore region from the shoreline through the surf zone out to the inner shelf and is characterized dynamically by the importance of waves and wave-driven flows. Recent work indicates that exchange between surf zone and inner shelf is predominantly due to transient and morphologic rip currents (Brown et al., 2015;Hally-Rosendahl & Feddersen, 2016), which are offshore-oriented flows generated in the surf zone that extend out beyond the breaker line. Quantifying the hydrodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 66 publications
2
15
1
Order By: Relevance
“…The χ 2 is sensitive to the cross-shore extent over which it is computed and increases for smaller surf zone widths. The χ 2 of the bathymetry observed on October 14 is ∼5 times larger than previous experiments with alongshore bathymetric variations described as small to moderate in Duck, NC and central California (Ruessink et al, 2001;Feddersen & Guza, 2003;O'Dea et al, 2021), and is >25 times larger than observed on a beach described as alongshore uniform (Spydell & Feddersen, 2009). On October 14 (November 16), the average shoreline position was approximately x = 108 m (110 m), and a single bar was located near x = 235 m (215 m) with an alongshore-variable trough near x = 175 m (170 m).…”
Section: Field Experimentscontrasting
confidence: 59%
See 4 more Smart Citations
“…The χ 2 is sensitive to the cross-shore extent over which it is computed and increases for smaller surf zone widths. The χ 2 of the bathymetry observed on October 14 is ∼5 times larger than previous experiments with alongshore bathymetric variations described as small to moderate in Duck, NC and central California (Ruessink et al, 2001;Feddersen & Guza, 2003;O'Dea et al, 2021), and is >25 times larger than observed on a beach described as alongshore uniform (Spydell & Feddersen, 2009). On October 14 (November 16), the average shoreline position was approximately x = 108 m (110 m), and a single bar was located near x = 235 m (215 m) with an alongshore-variable trough near x = 175 m (170 m).…”
Section: Field Experimentscontrasting
confidence: 59%
“…The cross-shore variability of eddy length scales has been investigated with models that account for the generation of eddies from short-crested wave breaking (Kumar & Feddersen, 2017;O'Dea et al, 2021). However, the vertical variability of eddy length scales is not known and has not been investigated using a three-dimensional phase-resolving model.…”
Section: Vertical Variability Of the Alongshore Wavenumber Spectra Of Vorticitymentioning
confidence: 99%
See 3 more Smart Citations